Cyclical short‐term fasting and refeeding effects on immunological alteration of the disk abalone, Haliotis discus discus - Dien Arista Anggorowati; Liqing Zang; Yutaka Tamaru; Takahiko Aoki; Fumiyoshi Okazaki (Aquaculture, Fish and Fisheries, 2025)
Abstract Starvation is a frequent challenge for many animals in their natural habitats. In aquatic ecosystems, certain fish and shellfish experience prolonged and short‐term starvation stress, particularly during periods of extreme weather in the wild and inadequate feeding practices in aquaculture systems. Nutritional deficiencies caused by either short‐term or prolonged starvation can lead to stress‐induced health issues in fish and shellfish. Our study aimed to assess the impact of repeated short‐term fasting and refeeding on immunological parameters and growth performance in the disk abalone, Haliotis discus discus. Abalones were randomly assigned to three distinct feeding patterns, with three replicates per group: Group I underwent continuous feeding for 35 days (CF), Group II experienced a repetitive cycle of 3‐day fasting and 4‐day refeeding for 35 days (PF) and Group III underwent no feeding for a 35‐day period (NF). We measured survival and growth rate as well as analysed immunological parameters, such as total haemocyte count, phenoloxidase activity, respiratory burst activity, lysozyme activity and protein content across the groups. The results indicated that different feeding treatments impacted these immune responses differently across groups. Specifically, the group exposed to NF experienced a significant reduction in total haemocyte count (THC), respiratory burst activity and protein concentration, whereas phenoloxidase activity and lysozyme activity were highest in this group. The CF group showed no significant changes in respiratory burst activity, protein content, phenoloxidase activity and lysozyme activity. In contrast, the cycling short‐term fasting and refeeding (PF) group exhibited higher lysozyme and phenoloxidase activities but had a lower THC. No differences were observed for respiratory burst activity and protein content in this group. This study demonstrated that the functionality of the innate immune system in abalone could be affected by nutritional status under starvation and refeeding.